2018
DOI: 10.1186/s13018-018-0885-z
|View full text |Cite
|
Sign up to set email alerts
|

The proper timing of second-stage revision in treating periprosthetic knee infection: reliable indicators and risk factors

Abstract: BackgroundTwo-stage revision is the standard procedure for periprosthetic knee infection. But when to perform the second-stage is still under debate. We attempt to search the reliable indicators, risk factors, and proper timing for the second-stage revision.MethodsWe reviewed and followed 81 infected total knee arthroplasty patients who underwent two-stage revision from January 2010 to January 2014. Our cohort included 56 males and 25 females, all patients were confirmed as PJI with the same phenotypic culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 20 publications
1
40
0
8
Order By: Relevance
“…In North America and East Asia, two-stage exchange arthroplasty is widely applied for chronic PJIs after TJA [3,4]. After removing the infected prosthesis and implanting an antibiotic-loaded spacer in the rst stage, the proper timing of reimplantation is crucial for successful treatment [5]. Currently, there is no "gold standard" to evaluate the eradication of PJI before reimplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In North America and East Asia, two-stage exchange arthroplasty is widely applied for chronic PJIs after TJA [3,4]. After removing the infected prosthesis and implanting an antibiotic-loaded spacer in the rst stage, the proper timing of reimplantation is crucial for successful treatment [5]. Currently, there is no "gold standard" to evaluate the eradication of PJI before reimplantation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reliability and utility of both indictors has been questioned by several studies. Due to their unclear threshold cutoff levels, the normalization of both markers was reported to fail to predict PJI control [5][6][7]11]. More than the ESR and CRP, several other serum biomarkers have been studied by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In North America and East Asia, two-stage exchange arthroplasty is wildly applied to chronic PJIs after TJA [3,4]. After removing the infected prosthesis and implanting an antibiotic-loaded spacer in first stage, the proper timing of reimplantation is crucial for successful treatment [5].So far, there is no gold reference to determine the eradication of PJI before reimplantation. The combination of serum indicators, synovial white cell count (WBC), culture results, intraoperative histology, and clinical symptoms is used extensively to guide the timing of reimplantation.…”
Section: Introductionmentioning
confidence: 99%
“…But the relativity and utility of both indictors was suspected by several researches. In spite of their doubtful threshold cutoff levels, the normalization of both markers was reported failed to predict control of PJI [5][6][7]11].Several other serum biomarkers were studied by researchers. Interleukin-6 (IL-6) was proved to be useful in diagnose PJI [12][13][14], and Hoell et al reported the good utility of IL-6 in predicting failure of reimplantation [15].…”
Section: Introductionmentioning
confidence: 99%
“…A definite PJI is present when: questioned by several studies. Due to their unclear threshold cutoff levels, the normalization of both markers was reported to fail predict PJI control [5][6][7]11].Several other serum biomarkers have been studied by researchers. Interleukin-6 (IL-6) was suggested to be useful in diagnosing PJI [12][13][14], and Hoell et al reported the high utility of IL-6 in predicting reimplantation failure [15].…”
Section: Introductionmentioning
confidence: 99%